Skills of 4Cs Prospective Manuscript Editors in the Era of Digitalization (Research of Language Error Analysis Course in MBKM Framework) - Meilan Arsanti; Ida Zulaeha; Subyantoro Subyantoro; Nas Haryati Setyaningsih (International Conference on Science, Education, and Technology, 2022)
Students of the Indonesian Language and Literature Education Study Program are strongly encouraged to become candidates for manuscript editors. In addition to the 4Cs skills, students must also have the proficiency of Indonesian language skills which can be obtained from the Language Error Analysis course. In this paper, three things are described, namely 1) 4Cs skills that must be mastered by students as a provision in pursuing the profession as a script editor other than as a teacher or educator, 2) the duties and roles of script editors in the era of digitalization, and 3) learning strategies for the Language Error Analysis course within the MBKM framework. The method used in this research is descriptive qualitative to dig up information related to the researched problem. Based on research that in addition to mastering good language skills, manuscript editors must also master skills that are in accordance with 21st century competencies, namely 4C to support their performance in the digitalization era. In this digitalization era, the role of the script editor is very important to maintain the dignity of the Indonesian language so that it is not influenced by foreign languages. These 21st century skills can be obtained from the lecture process and by applying internship programs at book publishers within the framework of Merdeka Belajar Kampus Merdeka (MBKM).